Multidirectional Instability in a Neglected Elbow Dislocation Managed with Circumferential Ligament Reconstruction. A Case Report - Krishna, Sathya Vamsi; Ballal, Madan; BR, Vivekanandea; HS, Chandrahsekar (Revista Brasileira de Ortopedia, 2020)
Neglected elbow dislocation is an uncommon condition and its treatment remains challenging. We present a case of a middle-aged woman presenting with neglected elbow dislocation and multi-direction instability in whom open reduction of the elbow joint and circumferential ligamentous reconstruction with a gracilis tendon graft was done. The functional outcome assessed with the Mayo elbow performance index was excellent. This circumferential technique is undoubtedly a viable technique and the indications can be extended to even manage a neglected dislocation. This procedure reduces the need or diminishes the duration of external fixation requirement and thereby encourages early mobilization.
Keywords: elbow joint; joint dislocation; joint instability; ligaments, articular